2022
DOI: 10.3390/ijms23147696
|View full text |Cite
|
Sign up to set email alerts
|

Binding Studies and Lead Generation of Pteridin-7(8H)-one Derivatives Targeting FLT3

Abstract: Ligand modification by substituting chemical groups within the binding pocket is a popular strategy for kinase drug development. In this study, a series of pteridin-7(8H)-one derivatives targeting wild-type FMS-like tyrosine kinase-3 (FLT3) and its D835Y mutant (FL3D835Y) were studied using a combination of molecular modeling techniques, such as docking, molecular dynamics (MD), binding energy calculation, and three-dimensional quantitative structure-activity relationship (3D-QSAR) studies. We determined the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Figure 4 a shows the generalized thermodynamic cycle of the relative binding free energy derivation scheme. In the earlier studies [ 23 , 24 ], we used an absolute binding free energy estimate in the modeling study of kinase inhibitors and found a satisfactory correlation between the experimental and computed binding free energies. Although, the calculated binding free energies were overestimated in comparison to the corresponding experimental values.…”
Section: Resultsmentioning
confidence: 89%
“…Figure 4 a shows the generalized thermodynamic cycle of the relative binding free energy derivation scheme. In the earlier studies [ 23 , 24 ], we used an absolute binding free energy estimate in the modeling study of kinase inhibitors and found a satisfactory correlation between the experimental and computed binding free energies. Although, the calculated binding free energies were overestimated in comparison to the corresponding experimental values.…”
Section: Resultsmentioning
confidence: 89%
“…Figure 4a shows the generalized thermodynamic cycle of the relative binding free energy derivation scheme. In the earlier studies [36,37], we used an absolute binding free energy estimate in the modeling study of kinase inhibitors and found a satisfactory correlation between the experimental and computed binding free energies, despite the high numerical approximation. Since the entire ligand needs to be perturbed (interactions off or on) corresponding to its surroundings, which requires a large number of λ intermediate states and simulation time.…”
Section: Relative Binding Affinity Estimationmentioning
confidence: 92%
“…GROMACS 2019.5 22 was used for the MD simulation study using Amber ff99SB force field according to our previous studies 23,24 . ACEPYPE 25 was used to parameterize the ligand molecules with AM1‐BCC charges.…”
Section: Methodsmentioning
confidence: 99%